Gene expression signature of primary imatinib-resistant chronic myeloid leukemia patients - Frank, Oliver; Brors, Benedikt; Fabarius, Alice; Li, Li; Haak, M.; Merk, S.; Schwindel, U.; Zheng, C.; Müller, Martin Christian; Gretz, Norbert; Hehlmann, Rüdiger; Hochhaus, Andreas; et al. (Leukemia, 2006)
Although the selective tyrosine kinase inhibitor imatinib is successfully used in the treatment of chronic myeloid leukemia (CML), inherent mechanisms confer primary resistance to leukemic patients. In order to search for potentially useful genes in predicting cytogenetic response, a retrospective gene expression study was performed. Leukocyte RNA isolated before imatinib from interferon-alpha-pretreated chronic phase CML patients (n=34) with or without major cytogenetic remission (⩽35% Philadelphia (Ph)+ metaphases) during the first year of treatment was comparatively analyzed using Affymetrix U133A chips. Using support vector machines for gene classification, an outcome-specific gene expression signature consisting of 128 genes was identified. Comparative expression data of specific genes point to changes in apoptosis (e.g. casp9, tumor necrosis factor receptor-associated protein 1, hras), DNA repair (msh3, ddb2), oxidative stress protection (glutathione synthetase, paraoxonase 2, vanin 1) and centrosomes (inhibitor of differentiation-1) within primary resistant patients. Independent statistical approaches and quantitative real-time reverse transcriptase-polymerase chain reaction studies support the clinical relevance of gene profiling. In conclusion, this study establishes a candidate predictor of imatinib resistance in interferon-alpha-pretreated CML patients to be subjected to future investigation in a larger independent patient cohort. The resulting expression signature point to involvement of BCR-ABL-independent mechanisms of resistance.
Gesehen am 10.05.2022